Achievement of ITER-relevant accelerated negative hydrogen ion current densities over 1000 s at the ELISE test facility. (25th June 2019) - Wünderlich, D.; Riedl, R.; Bonomo, F.; Mario, I.; Fantz, U.; Heinemann, B.; Kraus, W.
Abstract: The neutral beam heating system for the future international fusion experiment ITER will be based on radiofrequency driven ion sources delivering a large (≈1 × 2 m) and homogeneous negative hydrogen or deuterium ion beam of severals tens of amperes for up to 1 h. Such beams have never been produced before and a dedicated R&D process has been ongoing for more than two decades. An important intermediate step is the size scaling test facility ELISE (Extraction from a Large Ion Source Experiment) with its half-ITER size ion source. Recently, ELISE has fulfilled its first main aim, demonstrating hydrogen ITER-relevant accelerated negative ion current densities over 1000 s, at the required filling pressure of 0.3 Pa, with an electron–ion ratio below one and a beam homogeneity better than 90%. The measures identified as essential for achieving such pulses are the introduction of external permanent magnets and internal potential rods as well as a dedicated caesium conditioning technique.